Labelling dan Ras terhadap Identitas Budaya - Bakhrudin All Habsy; Dira Anindia Ayu Rosidin; Shofiyyah Qurrotul A’yun (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Labelling within a group greatly influences the formation of individual identity within that group. Labeling also has an influence on the assessment of a particular race and culture. Sometimes the impact of labelling on an individual can have a negative connotation, therefore the role of the counselor is needed as a liaison to provide education related to multicultural education. This research uses qualitative methods with literature study techniques. The purpose of this study is to determine the labelling that affects the cultural identity of individuals. The results of the study, containing (1) Definition of RAS, (2) Definition of Labelling, (3) Definition of Cultural Identity, (4) Effect of RAS on Cultural Identity, (5) Effect of Labelling on Cultural Identity, (6) The Counselor's Role in Overcoming Labelling.